Attachable roof for wheelchair / Muhammad Arsyad Abd Razak … [et al.] - Abd Razak, Muhammad Arsyad; Rozaidi, Aidi Zulkarnaen; Syed Shamsudin, Syed Fiross; Mohd Rahim, Najib; Mohd Yahizan, Faez; Ahmad Mokhtaza, Nur Akmal; Aminuddin, Raihah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Caregivers assisting individuals with disabilities encounter challenging conditions in the great outdoors of Malaysia, where rainfall can change suddenly to scorching sunshine. It is particularly difficult to manoeuvre a wheelchair while carrying an umbrella, particularly on winding paths or in crowded areas. Hence, the wheelchair needs the attachable roof to provide rain and sun protection. Caregivers are then able to concentrate on safely steering the wheelchair, as carrying an umbrella eliminates the additional burden and weight. The benefits are that the individual with a disability will no longer have to worry about getting wet, and the caregivers can maintain a steady grip on the wheelchair with both hands. This guarantees effortless movement. Furthermore, the weather in Malaysia can be extremely hot. Imagine attempting to keep a person in a wheelchair cool and shaded while pushing a wheelchair through the brutal sun. However, the attachable roof allows caregivers to offer shade while minimising physical effort. It is similar to possessing a portable shelter that follows the wheelchair wherever it goes. The Attachable Roof enhances outdoor usage in Malaysia for wheelchair users and caregivers by eliminating the inconvenience associated with umbrella carrying. It is a straightforward yet effective solution that promotes independence and comfort. Additionally, it fits the majority of wheelchairs and is simple to install, allowing anyone to use it efficiently. Caregivers are able to concentrate on organising memorable outdoor experiences with the assurance of dependable weather protection provided by the attachable roof on the wheelchair.